The state of food security and its determinants in Ghana: an ordered probit analysis of the household hunger scale and household food insecurity access scale - Jude Dokbila Kolog; Freda Elikplim Asem; Akwasi Mensah-Bonsu (Scientific African, 2023)
The issue of food insecurity has been well documented to be severe in northern Ghana. Several attempts have been made to curb the situation, but the effects of these interventions are unknown. Using responses from 405 rural households, this paper estimates the determinants of food insecurity in the Upper East region. Data were analysed using descriptive statistics and an ordered probit regression. The Household Food Security Access Scale (HFIAS) and the Household Hunger Scale (HHS) were the two measures of household food security used in the study. This paper validates and compares the two measures used to check whether determinants and status of household food security differ between the two measures. The findings show that the two measures of food security agreed on most of the significant determinants of household food security. Factors such as education of household head, households’ farm size, access to credit and access to extension services were significant determinants of household food security by both measures. Factors such as household size, access to good roads, access to formal cooperative and availability of paid jobs were found to be significant determinants of household food security with the HFIAS, while gender of household head and distance to market were significant determinants of food security in the HHS model. The study recommends improved education, social structures such as good roads and markets as well as support services such as credit and extension to combat food insecurity. These key steps should be taken as pillars to the sustainable implementation of Agenda 2063 for a food secure Africa.